(untitled) (Bangladesh Journal of Pharmacology, 2018)
This study was designed to understand whether the post-menopausal Chinese women (n=175) receiving tablet containing vitamin D (500 IU) and calcium (500 mg) had lower incidence of bone fracture compared to the post-menopausal Chinese women ((n=175) receiving a diet rich in calcium, vitamin D, and protein (milk, cheese, and yogurt, soybeans, spinach, fish including fatty fish, cheese, egg). This study assessed whether the levels of serum osteocalcin and urinary free deoxypyridinoline could be used as predictors of early bone trauma during post-menopausal period. After randomization, subjects were followed-up for up to 3 years to capture required data. The results suggested that therapeutic intervention (vitamin D and calcium) does not predict bone fracture among the post-menopausal Chinese women. However, correlation analysis revealed that the decreased level of serum osteocalcin and urinary free deoxypyridinoline were associated with higher incidence of fracture. The results suggest that the low level of serum osteocalcin and urinary free deoxypyridinoline cause increase susceptibility of fracture among the post-menopausal Chinese women.